Efektivitas Media Poster dalam Bimbingan dan Penyuluhan Islam Terhadap Pembentukan Karakter dan Pemahaman Keagamaan Mahasiswa - Rifatul Muna; Muhamad Rifa'i Subhi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Poster media, as a form of visual communication, is considered capable of conveying Islamic messages in an attractive, concise, and memorable manner, thereby strengthening the moral messages delivered by the counselor. This study aims to analyze the effectiveness of poster media in Islamic guidance and counseling in shaping students’ character and enhancing their religious understanding. This research employs a qualitative approach with a case study design, involving students who participate in Islamic guidance and counseling sessions utilizing poster-based materials. Data were collected through observation, in-depth interviews, and documentation, while data analysis followed the model of Miles, Huberman, and Saldaña (2014), which includes data condensation, data display, and conclusion drawing. To ensure the validity of the data, the researcher employed: (1) Source Triangulation; (2) Technique Triangulation; (3) Member Check; and (4) Peer Debriefing/Colleague Discussion. The findings indicate that the use of poster media is effective in shaping students’ character through the reinforcement of values such as honesty, discipline, responsibility, and proper conduct toward lecturers and peers. Additionally, the poster media improves students’ religious understanding related to noble character and the obligations of a Muslim. Factors influencing this effectiveness include appealing visual design, the relevance of the message to students’ needs, and the integration of posters within continuous guidance activities. The study concludes that poster media is an effective tool in Islamic guidance and counseling services and is recommended as a strategy for developing students’ character and religious awareness in higher education institutions.